Relationship between Regional Head Election Connectivity with Corruption Cultural Behavior in Indonesia - Hadi, Dejan Abdul; Hidayat, Faisal Syarif (Law Research Review Quarterly, 2019)
Post New Order era there was a demand for reform from the Indonesian people, which then led to changes in the concept of regional head election system in accordance with the basic mandate of organizing the Election of Regional Heads indirectly is based on the 1945 Constitution, Article 18 paragraph (4) after the amendment which reads "Governors, Regents, and Mayors respectively as Heads of Provincial, Regency and City Regional Governments are democratically elected "Then the concept of Pilkada after the enactment of Law No. 32 of 2004 in conjunction with Law No. 10 of 2016 ended the dominant influence of the Central Government. The arrival of the decentralization era and the system of direct regional elections made corrupt acts of collusion and nepotism a culture continue to spread to the area that is certain can threaten democracy and the existence of the NKRI. So the authors see a relationship between the concept of the concept of the regional head election system and the culture of corruption in Indonesia, so the solution to overcome this problem is strengthening corruption eradication institutions, strengthening at the regional level effectively, harmonizing legislation, strengthening the principle of general government principles good and enforcement of the rule of law with the principle of equality before the law by realizing that there is a very urgent need to overcome the culture of corruption.